2020
DOI: 10.1371/journal.pone.0239178
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative diagnoses and identification rates of unexpected gallbladder cancer

Abstract: Background Unexpected gallbladder cancer (UGBC) is sometimes found in the resected gallbladder of patients during or after surgery. Some reports have indicated UGBC identification rates for all gallbladder surgeries, but scarce data are available for the UGBC identification rates for specific gallbladder diseases. The present study was performed to clarify UGBC rates and the factors suspicious for UGBC categorized according to preoperative diagnoses, in patients undergoing laparoscopic cholecystectomy (LSC). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The number of calculi was less than 5 and the maximum diameter of calculi was less than 2 cm; patients and their families were fully informed of the study contents and signed relevant agreements. Exclusion criteria are as follows: patients with recurrent choledocholithiasis [ 14 , 15 ]; patients with other gallbladder diseases; patients with a history of abdominal surgery; patients with malignant tumors; female patients with choledocholithiasis in special physiological periods such as pregnancy, puerperium, and lactation; persons with mental illness; and those who refuse to sign informed consent [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The number of calculi was less than 5 and the maximum diameter of calculi was less than 2 cm; patients and their families were fully informed of the study contents and signed relevant agreements. Exclusion criteria are as follows: patients with recurrent choledocholithiasis [ 14 , 15 ]; patients with other gallbladder diseases; patients with a history of abdominal surgery; patients with malignant tumors; female patients with choledocholithiasis in special physiological periods such as pregnancy, puerperium, and lactation; persons with mental illness; and those who refuse to sign informed consent [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is because, there is a lot of confusion even in the textbooks and published literature about the exact definition of iGBC; some reports include even cases suspected on imaging, during the operation or in the GB specimen on naked eye examination in the operation theater as iGBC. [21][22][23] This needs to be corrected.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the frequency of IGBC was reported to be between 0.11% and 2.5%, [28][29][30][31][32][33][34][35] and Fujiwara et al reported that the incidence of IGBC in cholelithiasis was 0.054%, whereas in acute cholecystitis, the incidence was as high as 1.3%, with more advanced cases. 36 Figueiredo et al also reported that 49 (0.77%) of 6329 cholecystectomy cases had IGBC, and while 23 (0.38%) of 5931 were elective surgery cases, a higher rate of 26 (6.53%) of 398 were emergency surgery cases. 28 In recent years, EUS-guided gallbladder drainage (EUS-GBD) for acute cholecystitis has been performed in specialized centers, and the pooled proportion of perforations in a recent meta-analysis of EUS-GBD was 3.7%-6.7%.…”
Section: The Epidemiology Of Igbcmentioning
confidence: 92%
“…In 2019‐2020, seven case‐controlled studies (Table 1) and nine case‐series studies were published on IGBC. In these studies, the frequency of IGBC was reported to be between 0.11% and 2.5%, 28–35 and Fujiwara et al reported that the incidence of IGBC in cholelithiasis was 0.054%, whereas in acute cholecystitis, the incidence was as high as 1.3%, with more advanced cases 36 . Figueiredo et al also reported that 49 (0.77%) of 6329 cholecystectomy cases had IGBC, and while 23 (0.38%) of 5931 were elective surgery cases, a higher rate of 26 (6.53%) of 398 were emergency surgery cases 28 .…”
Section: Incidental Gallbladder Cancer (Igbc)mentioning
confidence: 96%